Pembinaan Usaha Nona.Nyinyir melalui Pengembangan Variasi Produk dan Promosi - Selvi Sel; Anita Maulina; Nur Fitri Rahmawati (Institut Ilmu Sosial dan Manajemen Stiami, 2021)
The Covid-19 pandemic has a negative impact on the economy. In this service, we help a teacher to develop his small business by empowering several housewives. We contributed to the development of product variations by conducting surveys on snacks desired by the community and promotions during the Covid-19 pandemic. Through this service, Nona.Nyinyir business was able to provide additional income for housewives of IDR 150,000 per week.